2016
DOI: 10.17352/2455-5495.000013
|View full text |Cite
|
Sign up to set email alerts
|

Does Milk Intake Play a Specific Role in the Pathogenesis of Kidney Stones?

Abstract: 026specifying the type). In addition, the variables collected for each patient and control provide demographic data (gender, age, height and weight) and information on the type of stones and the number of episodes of colic up to completion of the questionnaire (patients only) (Tables 1,2). Although the type of the kidney stones was not known in all the patients, most of the calculi analysed were calcium oxalate kidney stones, like observed in the general population (Table 1). Statistical analysisDescriptive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In line with our results, one study found that consuming dairy is associated with a reduced risk of kidney stones [ 22 ]. However, increased milk intake is recommended for uric acid-related stones [ 23 ]. Therefore, policies that promote a diet high in dietary alkali load can help reduce the risk of kidney stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, one study found that consuming dairy is associated with a reduced risk of kidney stones [ 22 ]. However, increased milk intake is recommended for uric acid-related stones [ 23 ]. Therefore, policies that promote a diet high in dietary alkali load can help reduce the risk of kidney stone formation.…”
Section: Discussionmentioning
confidence: 99%